Phage Therapy in the Era of Multidrug Resistance in Bacteria: A Systematic Review - Carlos Aranaga (International Journal of Molecular Sciences, 2022)
Bacteriophages offer an alternative for the treatment of multidrug-resistant bacterial diseases as their mechanism of action differs from that of antibiotics. However, their application in the clinical field is limited to specific cases of patients with few or no other alternative therapies. This systematic review assesses the effectiveness and safety of phage therapy against multidrug-resistant bacteria through the evaluation of studies published over the past decade. To that end, a bibliographic search was carried out in the PubMed, Science Direct, and Google Scholar databases. Of the 1500 studies found, 27 met the inclusion criteria, with a total of 165 treated patients. Treatment effectiveness, defined as the reduction in or elimination of the bacterial load, was 85%. Except for two patients who died from causes unrelated to phage therapy, no serious adverse events were reported. This shows that phage therapy could be an alternative treatment for patients with infections associated with multidrug-resistant bacteria. However, owing to the phage specificity required for the treatment of various bacterial strains, this therapy must be personalized in terms of bacteriophage type, route of administration, and dosage.